119k views
5 votes
Rewrite with only sin x and cos x.

cos 3x

cos x - 4 cos x sin^2 x
-sin^3 x + 2 sin x cos x
-sin^2 x + 2 sin x cos x
2 sin^2 x cos x - 2 sin x cos x

User Jimwan
by
6.0k points

1 Answer

7 votes

Answer:

correct Answer is A,
cos3x=cosx -4sinx^(2)* cosx

Explanation:

Theory:


cos(A+B)=cosA* cosB-sinA *sinB.


cos(A-B)=cosA* cosB+sinA *sinB.


sin(A+B)=sinA* cosB+cosA *sinB


sin(A-B)=sinA* cosB-cosA *sinB

By using above formula, we write as,


cos(2x)=cos(x+x)= cosx* cosx-sinx* sinx.


cos2x=cosx^(2) - sinx^(2)

Also,
sin2x=sin(x+x)=sinx* cosx+cosx* sinx


sin2x=2sinx* cosx

Now,


cos(3x)=cos(2x+x)=cos2x* cosx-sin2x*sinx


cos3x={cosx^(2) - sinx^(2)* cosx}-{2sinx* cosx* sinx}


cos3x= {cosx^(3) - sinx^(2)* cosx} - {2sinx^(2)* cosx}


cos3x= cosx^(3) - 3sinx^(2)* cosx


cos3x= cosx^(2)* cosx -3sinx^(2)* cosx


cos3x= (1-sinx^(2))* cosx -3sinx^(2)* cosx


cos3x= (cosx -sinx^(2)* cosx) -3sinx^(2)* cosx


cos3x=cosx -4sinx^(2)* cosx

thus, correct Answer is A,
cos3x=cosx -4sinx^(2)* cosx

User Vertexwahn
by
6.5k points